2014
DOI: 10.1242/jeb.104091
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned hearing sensitivity reduction in a bottlenose dolphin (Tursiops truncatus)

Abstract: The conditioned change in hearing sensitivity during a warning sound preceding a loud sound was investigated in the bottlenose dolphin. Hearing sensitivity was measured using pip-train test stimuli and auditory evoked potential recording. When the test/warning stimulus with a frequency of 22.5 or 32 kHz preceded the loud sound with a frequency of 22.5 kHz and a sound pressure level of 165 dB re. 1 μPa rms, hearing thresholds before the loud sound increased relative to the baseline. The threshold increased up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 33 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…Arguments in favor of the conditioned, rather than nonconditioned, nature of the observed hearing dampening were presented when the effect was previously described in a false killer whale (Nachtigall and Supin, 2013). Moreover, recently published data obtained in the same subject and under the same experimental conditions as in the present study have shown that the dependence of the effect on temporal inter-relations between the test/warning and loud sound indicates the conditioning nature of the observed dampening of hearing sensitivity (Nachtigall and Supin, 2014). The dampening effect did not depend on inter-trial intervals, i.e.…”
Section: Conditioned or Non-conditioned Effect?supporting
confidence: 67%
See 2 more Smart Citations
“…Arguments in favor of the conditioned, rather than nonconditioned, nature of the observed hearing dampening were presented when the effect was previously described in a false killer whale (Nachtigall and Supin, 2013). Moreover, recently published data obtained in the same subject and under the same experimental conditions as in the present study have shown that the dependence of the effect on temporal inter-relations between the test/warning and loud sound indicates the conditioning nature of the observed dampening of hearing sensitivity (Nachtigall and Supin, 2014). The dampening effect did not depend on inter-trial intervals, i.e.…”
Section: Conditioned or Non-conditioned Effect?supporting
confidence: 67%
“…Therefore, for the conditioning sessions, these faint sounds preceding the loud one are referred to as test/warning stimuli, and the 5-30 s time of their presentation is referred to as test/warning time. The 5-30 s test/warning time was used because this rather short warning resulted in successful conditioned hearing dampening, whereas longer warning (15-75 s, mean 45 s) resulted in a less prominent effect (Nachtigall and Supin, 2014). Within the chosen limits of durations, trial-by-trial randomization of the test/warning time served to exclude the linking of a conditioning effect to a particular time after the warning signal onset.…”
Section: Evoked Potential Features In the Conditioning Sessionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the orientation of the auditory bulla and air spaces in the head, the dolphins in the present study may have been positioning themselves in such a way as to shield their ears from the impulse and lower the effective received level. Anticipation and self-mitigation of an intense noise exposure has previously been demonstrated in a false killer whale (Nachtigall and Supin, 2013) and bottlenose dolphin (Nachtigall and Supin, 2014), although in these cases, no overt behavioral response was observed.…”
Section: Behavioral Observationsmentioning
confidence: 85%
“…A possible explanation for this is that the animals developed strategies to reduce hearing sensitivity that could not be observed behaviorally. In some cetacean species, for instance, the Pavlovian response to a warning signal preceding intense acoustic stimuli reduces hearing sensitivity (Nachtigall & Supin, , ), a possibility that has not been explored with pinnipeds. In contrast to previous studies, we used a relatively long CS tone that may have provided the animals with a relatively long warning period.…”
Section: Discussionmentioning
confidence: 99%